Early Spring Phytoplankton Dynamics in the Western Antarctic Peninsula. Issue 12 (1st December 2017) - Arrigo, Kevin R.; van Dijken, Gert L.; Alderkamp, Anne‐Carlijn; Erickson, Zachary K.; Lewis, Kate M.; Lowry, Kate E.; Joy‐Warren, Hannah L.; Middag, Rob; Nash‐Arrigo, Janice E.; Selz, Virginia; van de Poll, Willem
Abstract: The Palmer Long‐Term Ecological Research program has sampled waters of the western Antarctic Peninsula (wAP) annually each summer since 1990. However, information about the wAP prior to the peak of the phytoplankton bloom in January is sparse. Here we present results from a spring process cruise that sampled the wAP in the early stages of phytoplankton bloom development in 2014. Sea ice concentrations were high on the shelf relative to nonshelf waters, especially toward the south. Macronutrients were high and nonlimiting to phytoplankton growth in both shelf and nonshelf waters, while dissolved iron concentrations were high only on the shelf. Phytoplankton were in good physiological condition throughout the wAP, although biomass on the shelf was uniformly low, presumably because of heavy sea ice cover. In contrast, an early stage phytoplankton bloom was observed beneath variable sea ice cover just seaward of the shelf break. Chlorophyll a concentrations in the bloom reached 2 mg m −3 within a 100–150 km band between the SBACC and SACCF. The location of the bloom appeared to be controlled by a balance between enhanced vertical mixing at the position of the two fronts and increased stratification due to melting sea ice between them. Unlike summer, when diatoms overwhelmingly dominate the phytoplankton population of the wAP, the haptophyte Phaeocystis antarctica dominated in spring, although diatoms were common. These results suggest that factors controlling phytoplankton abundance and composition change seasonally and may differentially affect phytoplankton populations as environmental conditions within the wAP region continue to change. Key Points: Phytoplankton in the wAP in spring are physiologically competent but limited by light availability Despite low springtime iron concentrations, phytoplankton showed no signs of physiological stress Phytoplankton bloom development in spring was determined by ice cover and a balance between vertical mixing and stratification